Inna Rosja — alternatywne rozwiązania polityczne i przyszłość Rosji według Eduarda Limonowa - Dańda, Aleksander (Przegląd Rusycystyczny, 2012)
Aleksander Dańda Wyższa Szkoła Europejska im. ks. J. Tischnera, Kraków, Poland adanda@wse.krakow.pl Другая Россия — альтернативные политические решения и будущего России по Эдуарду Лимонову Резюме национально-большевистская партия и ее лидер Эдуард лимонов, выступающая в настоящее время с преобразованной программой как другая россия, является силой, которая разбивает идеализированный образ окциденталистской антипутинской оппозиции. как лимонов, человек, рожденный во время Сталина, представляет себе политическоe будущее россии, освобожденной от власти путина? какие потен-циальные сценарии развития политической ситуации в россии указывает он своим партийным товарищам и простым россиянам? настоящая статья отвечает на эти во-просы, анализируя тексты самого лимонова: программу партии другая россия (2010), избирательной программы лимонова в президентских выборах в россии в 2012 г. и произведений лимонова с особым учетом его сборников Убийство часового (1993) и Другая Россия (2003). THE OTHER RUSSIA — THE VISION OF POLITICAL ALTERNATIVES AND THE FUTURE OF RUSSIA ACCORDING TO EDUARD LIMONOV Summary The National Bolshevik Party together with its creator and leader, Eduard Limonov, acting presently under the changed name and modified programme as The Other Russia party, is a political grouping which damages the ideal picture of pro-western anti-Putin opposition. How does the man born in the times of Stalin, perceive the political future of Russia freed from Putin? What kind of political scenarios for Russia does he present to his die-hard followers as well as to the ordinary Russians? This paper answers the aforementioned research questions basing on the analysis of the texts authored by Limonov himself: the political programme of The Other Russia party of 2010, the programme of Limonov for the 2012 presidential elections and chosen Limonov’s books with special attention given to the political ones: The Sentinel’s Murder (1993) and The Other Russia (2003).